Descriptions of two new species of Gyrocarisa (Trichoptera: Petrothrincidae) from Madagascar - Malm, Tobias; Johanson, Kjell Arne (Zootaxa, 2005)
Two new species of the Malagasy endemic genus Gyrocarisa (Trichoptera: Petrothrincidae), Gyrocarisa scottae, new species, and Gyrocarisa weaveri, new species, are described and illustrated. A key to the males of the known species of Gyrocarisa, and additional records of G. stenieri Weaver and G. acuta Weaver are given.